A Model to Predict Plant-available Water Content of Soils at Different Land Units in Bengkulu, Indonesia - Bandi Hermawan; Hasanudin Hasaanudin; Indra Agustian; Bambang Gonggo Murcitro (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2020)
Soil water availability to the plants is a very important physical property of soil that controls water and nutrient absorption by the plant. It is defined as the difference between the maximum amount of water the soil can hold and the minimum condition that the plant can no longer extract water from the soil. However, soil factors that control the plant available water content (PAWC) in the soil have not been fully understood. The present study aims to analyze the relations between particle-size distributions and organic carbon with the available water of the soil and to develop a model of predicting PAWC. Five soil profiles at different land units were described up to the depth of 100 cm. Ten undisturbed soil samples were taken using the stainless-made core sampler from 10 cm increments for the soil water holding capacity analysis. A similar number of disturbed samples were also provided from the same depths for soil texture and organic carbon analysis. Results showed that the variance in PAWC could be explained by sand and clay fractions (R2>0.35) but not by silt and organic carbon contents. Therefore, we were able to develop a model for the prediction of available water content in the soil from the sand and clay parameters. The model will help decision-makers be able to propose conservation and management strategies for PAWC in agricultural practices as well as for the soil moisture retention at civil works.